2011
DOI: 10.2172/1009749
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory and Modeling Evaluations in Support of Field Testing for Desiccation at the Hanford Site

Abstract: The Deep Vadose Zone Treatability Test Plan for the Hanford Central Plateau 1 includes testing of the desiccation technology as a potential technology to be used in conjunction with surface infiltration control to limit the flux of technetium and other contaminants in the vadose zone to the groundwater. Laboratory and modeling efforts were conducted to investigate technical uncertainties related to the desiccation process and its impact on contaminant transport. This information is intended to support planning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(83 citation statements)
references
References 25 publications
6
77
0
Order By: Relevance
“…Because the transport of dry gas is directly related to the permeability of the porous medium, higher permeability zones in soil columns and flow cells packed with heterogeneous media dried more quickly than lower permeability zones (Oostrom et al, 2009, 2012a,2012b). Modeling studies (Ward et al, 2008; Truex et al, 2011) demonstrated that the desiccation rate is increased with higher temperature and lower relative humidity of the injected dry gas, consistent with laboratory studies where the thermodynamic factors controlling the water‐holding capacity of the injected dry gas were correlated with the desiccation rate (Ward et al, 2008; Oostrom et al, 2009, 2012a,2012b; Truex et al, 2011). Laboratory studies have also demonstrated that the concentration of solutes in the pore water does not significantly affect the desiccation rate for solute concentration ranging up to 5.8M of NaNO 3 (Truex et al, 2011).…”
supporting
confidence: 78%
See 3 more Smart Citations
“…Because the transport of dry gas is directly related to the permeability of the porous medium, higher permeability zones in soil columns and flow cells packed with heterogeneous media dried more quickly than lower permeability zones (Oostrom et al, 2009, 2012a,2012b). Modeling studies (Ward et al, 2008; Truex et al, 2011) demonstrated that the desiccation rate is increased with higher temperature and lower relative humidity of the injected dry gas, consistent with laboratory studies where the thermodynamic factors controlling the water‐holding capacity of the injected dry gas were correlated with the desiccation rate (Ward et al, 2008; Oostrom et al, 2009, 2012a,2012b; Truex et al, 2011). Laboratory studies have also demonstrated that the concentration of solutes in the pore water does not significantly affect the desiccation rate for solute concentration ranging up to 5.8M of NaNO 3 (Truex et al, 2011).…”
supporting
confidence: 78%
“…In addition to rewetting from aqueous‐phase movement, rewetting can also occur through movement of vapor‐phase moisture (humid soil gas). Truex et al (2011) demonstrated that vapor‐phase rewetting can increase the moisture content to near the residual moisture content of tested porous media. However, the vapor‐phase rewetting process is also very slow without soil gas advection because of the relatively low moisture content of soil gas and slow diffusion‐driven movement of the humid gas.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Similar to the BY Cribs example, lateral spreading diminishes moisture conditions as an attenuation mechanism and an assessment of moisture conditions and porous media properties could be used to assess current fluxes in relation to the fluxes expected under long-term recharge-driven conditions (e.g., to assess whether future fluxes are expected to resemble Figure 1A or Figure 1B). The BC Cribs and Trenches site has been the focus of vadose zone investigations (e.g., Ward et al 2004;Truex et al 2011bTruex et al , 2012. These efforts have included simulation of water and Tc-99 flux to groundwater (Ward et al 2004).…”
Section: Uranium Contamination Near the Bx Tank Farm (Bx-102)mentioning
confidence: 99%